FOLIAR COMPOSITION OF Eucalyptus urograndis IN TWO SITES FERTILIZED WITH N, P AND K IN SOUTHERN BRAZIL - Martins Bassaco, Marcos Vinícius; Vargas Motta, Antonio Carlos; Nisgoski, Silvana; Ferreira, Carla Fernanda; Pereira, Milena (Floresta, 2019)
The leaf composition has been used as a tool in establishing the nutritional diagnosis and evaluation of the effectiveness of the use of nutrients. This knowledge is still scarce in subtropical conditions of cultivation. In this sense, the study aims to evaluate the effect of N, P and K fertilization on leaf concentration of Eucalyptus urograndis. The experiments were installed in the Oxisols of the sandy-loam texture, in the counties of Jaguariaíva and Ventania, state of Paraná. In the N and P experiments, the following doses: 0; 30; 60; 120 and 240 kg ha-1 of N and P2O5; and 0; 35; 70; 140 and 280 kg ha-1 K2O, split in four applications: during planting and side dressing at 3, 9 and 12 months of age. The response was evaluated according to the nutritional status of the plants at 12, 24 and 36 months, by foliar concentration. It also evaluated levels of K deficiency plant through visual and chemical analysis. The application of N and P did not result in alteration in the leaf contents of the same in all evaluated periods and in the two regions, with a slight decrease in the concentrations with time. A different effect occurred with K at the Jaguariaíva site, which altered its foliar concentration at the 24th and 36th month, and increased foliar concentrations with time. These effects demonstrate that foliar diagnosis, through foliar concentrations, may present limitations of interpretation and should not be evaluated separately for fertilization recommendation.